The Link between Government Spending, Consumer Confidence and Consumption Expenditures in Emerging Market Countries - (:unkn) unknown (SAVEZ EKONOMISTA VOJVODINE, 2010)
The impact of government spending on private consumption is extensively studied in the literature. However, the main theme of these studies is the possible crowding-in or crowding-out impact of government spending on consumer spending. This paper attempts to introduce a new variable to this well-known literature by investigating the existence of a relationship between government expenditure, consumer spending and consumer confidence for a group of emerging market countries. We examine whether a change in consumer confidence causes any change in government spending. Moreover, we analyze whether there is a feedback from government spending and private consumption to consumer confidence. Our empirical findings demonstrate the important role of consumer confidence on government spending and private consumption expenditures.
Keywords: Government spending; Consumer confidence; Consumption spending; UNIT-ROOT TESTS; PRIVATE CONSUMPTION; COINTEGRATION ANALYSIS; PANEL COINTEGRATION; FISCAL-POLICY